Editorial: Bioethical contributions in health conflict situations - Giustina, Tatiana Bragança de Azevedo Della (2021)
This is our last issue of 2021 – a year of many efforts against the COVID-19pandemic, vaccination, and many important reflections.This editorial begins with a topic that has been widely discussed, as it involves bioethical issues: an analysis of the pandemic and bioethical considerations about early treatment. Without polemicizing and adopting the Opinion of the Brazilian Federal Council of Medicine (CFM) 4/2020 1, it is not about supporting or not the use of any medication, but about the bioethical pillar of physician and patient autonomy, especially when the principles of beneficence and non-maleficence are observed. That is, a true “therapeutic alliance” between physician and patient should be implemented to always comply with the guidelines provided by evidence-based medicine.